Avaliação da qualidade de vida em pacientes submetidos a clareamento dental caseiro – revisão sistemática e metanálise - Matick Rombaldo, Anna Carolina Cenci (2022)
At-home tooth bleaching provides esthetic benefits to patients and can help to improve their self-esteem and self-confidence. It is also a simple and effective treatment with great short-term results. Although it may present some risks, it is considered a safe and minimally invasive method. OBJECTIVE: To assess, through a systematic review and metaanalysis, whether patients subjected to at-home tooth bleaching had their quality of life improved. MATERIALS AND METHOD: The studies were searched in the following electronic databases (until June 2021): MEDLINE (via PubMed), Cochrane Library, Brazilian Dental Library, Latin American and Caribbean Literature on Health Sciences (LILACS), and citation databases (Scopus, Web of Science and EMBASE). The studies were selected according to their titles, without language restrictions. Study quality was assessed with the Cochrane Collaboration tool to detect the risk of bias. STATISTICAL TREATMENT: The data was analyzed with the RStudio statistical software and summarized by calculating the standardized mean difference for continuous data and risk ratio and, along with the 95% confidence interval, for dichotomous data, using a random-effects model expressed in tables and graphs. RESULTS: Duplicates were removed and two reviewers selected the studies that met the inclusion criteria. Of the 68 full-text articles evaluated, 13 remained and were analyzed for initial results. Of these, one article had a high risk of bias, one had a low risk, and the other 11 had an uncertain risk. Of the 13 articles evaluated, seven were part of the meta-analysis and presented 87% of patient satisfaction after bleaching. CONCLUSION: There was an improvement in the quality of life of patients subjected to at-home tooth bleaching.